2014
DOI: 10.1103/physrevlett.112.188301
|View full text |Cite
|
Sign up to set email alerts
|

Critical Onset of Layering in Sedimenting Suspensions of Nanoparticles

Abstract: We quantitatively study the critical onset of layering in suspensions of nanoparticles in a solvent, where an initially homogeneous suspension, subject to an effective gravity a in a centrifuge, spontaneously forms well-defined layers of constant particle density, so that the density changes in a staircaselike manner along the axis of gravity. This phenomenon is well known; yet, it has never been quantitatively studied under reproducible conditions: therefore, its physical mechanism remained controversial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The herein observed phenomena of non-ideality in AC experiments is not new and was recently discussed in detail by Butenko et al 33 It was shown that temperature gradients can induce such convection, which can be followed by layering in the measurement cell. 34 This in turn will affect the width of distributions or can even result in false peaks.…”
Section: Assessment Of Particle Size Distributions and Monitoring Of mentioning
confidence: 50%
“…The herein observed phenomena of non-ideality in AC experiments is not new and was recently discussed in detail by Butenko et al 33 It was shown that temperature gradients can induce such convection, which can be followed by layering in the measurement cell. 34 This in turn will affect the width of distributions or can even result in false peaks.…”
Section: Assessment Of Particle Size Distributions and Monitoring Of mentioning
confidence: 50%
“…It is useful to point out that, in the presence of even minimal lateral temperature gradients, a stretching interface may become unstable, leading to stratification and formation of a banded profile. Although known for almost a century [27], this curious effect has usually been observed for extremely dilute dispersions, where substantial spreading of the interface takes place before it reaches a time-invariant shape [28,29]. Our evidence suggests that stratified settling may also occur in rather concentrated suspensions of strongly attractive monodisperse particles.…”
mentioning
confidence: 56%
“…Few reports argue that the formation of such steps can allude to convective instabilities leading to the formation of layers during sedimentation. For instance, Butenko et al [59] noticed the formation of successive plateaus, when they measured Cu-Ag nanoparticles. It is reported that such convective instabilities arise primarily due to (i) temperature gradients across the cuvette and (ii) rectangular shaped sample cell.…”
Section: Tem Imaging Of Inksmentioning
confidence: 99%